SONG ANALYSIS ON THE PRESENTATION OF POMPANG MUSIC - Andi Ihsan (Universitas Negeri Makassar, 2022)
This study aims to analyze the song on the presentation of Pompang music in Mamasa district. The research approach is to use descriptive qualitative research methods where data collection, is done through document studies, observations, and interviews, including recording research activities. This study focuses on the intra-musical analysis of the presentation of pumping music, especially the type and structure of the song and how the composition of the musical aspects. Data analysis is done by reduction, display, and verification. The results of the research are the types of songs that are played in the presentation of Pompang music, namely songs in the form of Maras and Hymns. The song Maras is presented without lyrics and vocals, while the hymn uses poetry with the main melody dominated by a flute. In the presentation of the music, each group of instruments has a pattern of rhythm, harmony, and melody that influence each other and form the uniqueness of pumping music.